Rhino-Orbital Cerebral Mucormycosis in a Patient With Diabetic Ketoacidosis: A Case Report and Literature Review - Dong, Nan; Jordan, Ashly E.; Shen, Xiaozhu; Wu, Xuan; Guo, Xianghong; Zhao, Hongru; Wang, Yajuan; Wang, Dapeng; Fang, Qi (Frontiers in Neurology, 2022)
Background: Rhino-orbital Cerebral Mucormycosis (ROCM) is a rare invasive and fatal fungal disease. Due to the lack of specific clinical manifestations and adequate auxiliary examinations, patients are easily misdiagnosed in the early stage. Early diagnosis and timely therapy are essential for successful treatment. Case report: We report a 68-year-old man with diabetic ketoacidosis, presented with orbital apex syndrome (OAS), fever, and pansinusitis, progressively worsened to death only four days after admission. It was finally confirmed as a fungal Rhizopus arrhizus infection by Metagenomics Cell-free DNA next-generation sequencing (mNGS) testing. Conclusion: Orbital apex syndrome (OAS) could be the initial presentation for mucormycosis. Thus, it’s necessary to evaluate the presence of mucormycosis for patients with OAS, especially in diabetic or immunosuppressed hosts, mNGS testing and timely antifungal therapy should be strongly recommended in highly suspected cases.